A guide to IPM in French beans production, with emphasis on Kenya - Seif, Abdurabi; Varela, Ana M.; Michalik, Susanne.; Löhr, Bernhard (International Centre of Insect Physiology and Ecology, 2002)
French beans are a major export crop in many African countries. This pocket manual summarises common pests and diseases of the crop and recommends IPM methods that can be used to combat them and meet the increasingly stringent regulations imposed by importers, such as the EU, on pestcide residue levels in vegetables.